Abstracts from the World Scientific Congress of Golf VII, St. Andrews, Scotland, July 18-22, 2016 (International Journal of Golf Science, 2016)
The mission of the WSCG is to bring together researchers, professionals, and interested golfers in the areas of The Golfer, The Golf Course, and Equipment and Technology. The table of contents lists three keynote speeches, nine tutorials and more than 60 papers on different aspects of golf science. For instance - research on Quiet Eye and putting. It`s a concept that a fair amount of research has been done on, but when I sat in on a presentation from Laura Carey she presented some valid arguments to take another look at the concept. In her study they attempted to create a representative task (previous studies haven`t taken this into account) to what golfers face on the course, putts of different lengths and slope (8, 15, and 25 feet) and what they found was surprising. The data revealed considerable within-participant variability in both QE and performance measures. The within variability of participants in putts holed and QE highlight that within experienced amateur and professional golfers there is inconsistency within their putting accuracy and their routines. (Laura Carey, Robin Jackson, Malcolm Fairweather, Joe Causer & Mark Williams, 2016). What they found was a lot of variation and variability with the duration of Quiet Eye amongst golfers. At this point it seems we don`t understand why it works or why it happens. Or the concept of "external focus": The concept being that an external focus helps to make movements more fluid and improve performance + learning. Dr. Noel Rousseau presented some very interesting research that might open up some new possibilities. In a study he did he created an "intervention" of sorts walking golfers through a pre-shot routine helping them limit conscious processing (swing thoughts). You might think that if you had "no thoughts" during a swing you would be able to perform better. What he found is that`s not true for everyone… A high `verbaliser` group deteriorated while `visualisers` showed improvement during restricted conscious processing trials (Noel Rousseau, Matthew Bridge & Ian Boardley, 2016). Dr. Bob Christina and Eric Alpenfels from Pinehurst went about busting a number of myths with their research. Here are a couple of the most interesting ones that will probably have an impact on game results. Aim Small Miss Small? In the testing they did this didn`t hold true… in fact the opposite appeared to have the most positive impacts with driving and long putting. Lower Tee Height = More Accuracy? Not only do golfers hit it longer but also more accurately when teeing the ball up higher. This again goes against conventional wisdom but showed to be true with their testing. Use the grip size that feels best? Most people choose their grip size by what feels best or based on some type of fitting chart. Through testing 23/24 golfers found they had their best performance with a grip other than what they were fit for based on measurements. The reality is that selecting the right grip size has less to do with preference or size of hands and has more to do with the type of shot and performance. Another topic was The Brain and Emotions Control Learning and Performance by Michael Hebron & Stephen Yazulla. Some interesting insights to share on learning and the brain: 1) To be mindful that your words and attitudes create emotional responses in your students during a lesson, particularly those attempts that would be considered to be "failed" outcomes. 2) To understand that these emotional responses are reflected in the hormonal environment of the brain, which in turn affect subsequent actions. 3) To coach in a manner that takes these changes in the brain into account so as to create a learning environment that enhances learning and performance rather than suppressing them. FROM A REVIEW BY C. WALKER